2016
DOI: 10.1105/tpc.16.00012
|View full text |Cite
|
Sign up to set email alerts
|

Global regulation of plant immunity by histone lysine methyl transferases

Abstract: Posttranslational modification of histones modulates gene expression affecting diverse biological functions. We showed that the Arabidopsis thaliana histone methyl transferases SET DOMAIN GROUP8 (SDG8) and SDG25 regulate pep1-, flg22-, and effector-triggered immunity as well as systemic acquired resistance. Genome-wide basal and induced transcriptome changes regulated by SDG8 and/or SDG25 showed that two genes of the SDG-dependent transcriptome, CAROTENOID ISOMERASE2 (CCR2) and ECERIFERUM3 (CER3), were also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 79 publications
(112 reference statements)
1
91
0
Order By: Relevance
“…We also detected in sdg8-1 an increased susceptibility and bacterial growth at 3 dpi when the virulent strain Pst DC3000 was used (Figures 1A,B). Previously, similar observations were made when the allelic mutant lines sdg8-2 (Palma et al, 2010;Lee et al, 2016) and sdg8-4 (De-La-Peña et al, 2012) were infected with Pst. In addition, we noted that sdg8-1 supported higher growth of the virulent than the avirulent Pst strain (Figure 1B), suggesting that ETI still operate in the mutant, but less efficiently than in WT plants.…”
Section: Sdg8 Mutation Increases Susceptibility To Pseudomonas Infectionsupporting
confidence: 70%
See 2 more Smart Citations
“…We also detected in sdg8-1 an increased susceptibility and bacterial growth at 3 dpi when the virulent strain Pst DC3000 was used (Figures 1A,B). Previously, similar observations were made when the allelic mutant lines sdg8-2 (Palma et al, 2010;Lee et al, 2016) and sdg8-4 (De-La-Peña et al, 2012) were infected with Pst. In addition, we noted that sdg8-1 supported higher growth of the virulent than the avirulent Pst strain (Figure 1B), suggesting that ETI still operate in the mutant, but less efficiently than in WT plants.…”
Section: Sdg8 Mutation Increases Susceptibility To Pseudomonas Infectionsupporting
confidence: 70%
“…Four HKMTs, exclusively from the TrxG group were so far reported to directly or indirectly contribute to the regulation of plant immunity, with their corresponding mutant being more susceptible to some pathogens (Alvarez-Venegas et al, 2007;Berr et al, 2010;Palma et al, 2010;De-La-Peña et al, 2012;Xia et al, 2013;Lee et al, 2016). Among them, the H3K36 di-and tri-methyltransferase SET DOMAIN GROUP 8 (SDG8) was involved in many biological processes, including the regulation of flowering time, organ growth, ovule and anther development, seed development, carotenoid biosynthesis, brassinosteroid-regulated gene expression, light-and/or carbonresponsive gene expression and RNA processing in response to temperature or nitrate signaling (Soppe et al, 1999;Zhao et al, 2005;Dong et al, 2008;Xu et al, 2008;Cazzonelli et al, 2009b;Grini et al, 2009;Tang et al, 2012;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others, both H3K4me3 and H3K36me3 are associated with active transcription of flowering time genes (He, 2009;Berr et al, 2011). Loss-of-function of SET DOMAIN GROUP 8 (SDG8), which encodes a major H3K36methyltransferase in Arabidopsis, leads to early flowering (Kim et al, 2005b;Zhao et al, 2005;Xu et al, 2008) and reduced resistance to pathogens (Berr et al, 2010a;Palma et al, 2010;Lee et al, 2016), two phenotypes similar to the ones described in hub1/hub2 mutants.…”
Section: Introductionmentioning
confidence: 87%
“…Histone modifications potentially provides a reversible and dynamic way to regulate many biological processes including plant immunity (Ramirez‐Prado et al , ). In Arabidopsis, histone deacetylase HDA6 (Wang et al , ), HDA19 (Zhou et al , ; Choi et al , ), methyltransferases ATX1 (Alvarez‐Venegas et al , ), ATXR7 (Xia et al , ), SDG8 (Berr et al , ) and SDG25 (Lee et al , ), demethylases FLD (Singh et al , ) and JMJ27 (Dutta et al , ), and H2B monoubiquitinase HUB1 (Dhawan et al , ; Zou et al , ), have been previously shown to affect plant resistance. In this study, we have discovered that JMJ14 is a positive regulator of plant immunity.…”
Section: Discussionmentioning
confidence: 99%